Te Rongyos Elet!... - Bacsó, Péter (Hungary : Dialóg Filmstúdió / Mafilm, 1983)
This is a satire of Hungary in the 1950s. Lucy Sziráky is a talented successful actress. Unfortunately the communist secret police find out that she married once a count and deport her to a farming village for re-education as an enemy of the people. The other deported aristocrats do not receive her with joy and it takes a while for Lucy to have herself accepted by the community. Additionally, she also gets involved with a string of lovers, everyone from a police chief to a former baron -- apparently rehabilitation is not always what it seems.
Duration: 01:48:00
Keywords: Fiction films